Interactive articulate storyline application based on real world problem and local Ngada wisdom - Kua, Maria Yuliana; Dolo, Fransiskus Xaverius; Suparmi, Ni Wayan; Gelu, Afrianus; Dhena, Gervarsia V. A.; Meme, Yosefina Owa (Univeritas Papua, 2024)
Teachers need quality online learning for practical, fun, and contextual science learning. Therefore, this research aims to analyze product suitability retrieved from validation results by material, media, learning design, and language experts, as well as product trial results by user candidates. A research and development (R&D) approach based on Kurt's ADDIE model was used to achieve this research aim. The subjects were 5 teachers and 20 Citra Bakti Junior High School students. We employed data collection strategies through the use of validation sheets, questionnaires, validation evaluation sheets, and prospective user response surveys. The data analysis employed descriptive and inferential statistics. The research results show that the average validation score from material experts is 4.60, media experts are 4.50, learning design experts are 4.35, and language experts are 4.48, all of which are in the very good range. Additionally, teachers' and students' average outcomes trial scores were 4.49 and 4.54, respectively, at an excellent level. Given this information, the interactive, articulate storyline product based on real-world problems and the local wisdom of “Ngada” is suitable for application in the online learning process.